2013
DOI: 10.1002/cb.1433
|View full text |Cite
|
Sign up to set email alerts
|

Online lifestyle consumption community dynamics: A practice‐based analysis

Abstract: The purpose of this study is to identify and categorize the discursive practices through which consumers negotiate a lifestyle-related identity in online lifestyle consumption communities. The empirical case is a very active community of consumers who adhere to the Low Carb -High Fat (LCHF) diet. The paper contributes to communal consumption literature by showing how a lifestyle identity and the community evolve together. Focusing on an online community with lifestyle focus differentiates this study from previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 55 publications
0
44
0
2
Order By: Relevance
“…The first component in the framework is the variable community belonging. Research has been emphasizing the emerging role of collective co-production (Peters et al, 2012) and community belonging (Närvänen et al 2013) on consumption behavior. Community memberships or the aspiration to be part of a group or community is argued to be one determinant of practicing sharing or collaborative consumption activities (Ostrom, 1990;Nelson and Rademacher, 2009;Galbreth et al, 2012).…”
Section: Collaborative Consumptionmentioning
confidence: 99%
“…The first component in the framework is the variable community belonging. Research has been emphasizing the emerging role of collective co-production (Peters et al, 2012) and community belonging (Närvänen et al 2013) on consumption behavior. Community memberships or the aspiration to be part of a group or community is argued to be one determinant of practicing sharing or collaborative consumption activities (Ostrom, 1990;Nelson and Rademacher, 2009;Galbreth et al, 2012).…”
Section: Collaborative Consumptionmentioning
confidence: 99%
“…Not only are online transactions in web stores acquiring considerable momentum, but consumers also allocate an increasing amount of time to other online activities. Consumers read product reviews, follow blogs and join online communities, sharing their views and opinions with others (Kozinets, Hemetsberger, & Schau, 2008;Kozinets, De Valck, Wojnicki, & Wilner, 2010;Kulmala, Mesiranta, & Tuominen, 2012;Scaraboto & Fischer, 2013;Närvänen, Kartastenpää, & Kuusela, 2013). Hence, shopping is only one consumption practice among many others.…”
Section: Introductionmentioning
confidence: 99%
“…group interview participants commented on the social ties, yet heterogeneous nature, and conflict and debate evident in the community. These characteristics have been found in the lifestyle consumption communities identified in previous research (Heinonen 2011;Närvänen, Kartastenpää, and Kuusela 2013). The study identified ubiquitous alcohol marketing activity used to associate and embed alcohol brands within the NRL community.…”
Section: Discussion Implications Limitations and Future Research DImentioning
confidence: 89%
“…More recently, the idea of lifestyle consumption communities has been identified (Närvänen, Kartastenpää, and Kuusela 2013). Despite acknowledgement of the often fluid and hybrid nature of consumption communities (Canniford 2011), there is less research examining structures that may overlap or coincide -for example when commercial brands engage existing consumption communities.…”
Section: Introductionmentioning
confidence: 98%